Training healthcare professionals in LGBTI cultural competencies: Exploratory findings from the Health4LGBTI pilot project. Issue 5 (May 2020) - Donisi, Valeria; Amaddeo, Francesco; Zakrzewska, Karolina; Farinella, Francesco; Davis, Ruth; Gios, Lorenzo; Sherriff, Nigel; Zeeman, Laetitia; Mcglynn, Nick; Browne, Kath; Pawlega, Michal; Rodzinka, Marcin; et al.
Highlights: The Health4LGBTI training is a cultural competencies course for healthcare professionals. The Health4LGBTI training course increased knowledge on LGBTI health and inequalities. The Health4LGBTI training course improved attitudes toward LGBTI people. Both clinical and support staff can benefit from the Health4LGBTI training. Abstract: Objectives: Lesbian, gay, bisexual, trans and intersex (LGBTI) people experience health inequalities and barriers to accessing healthcare at a greater rate than the general population. This paper aims to present the Health4LGBTI training course for healthcare workers and the results of its pilot implementation. Methods: Funded by the European Parliament, the training course was developed by a multidisciplinary team including LGBTI organisations as part of the Health4LGBTI Project. 110 healthcare professionals from diverse medical fields attended the pilot training in six European Member States. Knowledge and attitudes were compared on the basis of a pre-post evaluation design utilising an ad hoc questionnaire. Results: Knowledge scores increased after the training, irrespective of age and sexual orientation of participants. Attitudes scores generally improved, particularly in terms of inclusivity and a greater acknowledgement of LGBTI health needs and self-competence. Conclusion: The Health4LGBTI training course is both feasible and effective in training healthcare professionals and support staff to improve cultural competence and thereby promoting inclusive healthcare practice. Practice Implications: The Health4LGBTI training course can be implemented in different healthcare contexts. Piloting of the course provided an opportunity for healthcare professionals and for support staff to improve their knowledge of, and attitudes towards, LGBTI people.